Pengaruh Asupan Karbohidrat Terhadap Kadar Glukosa Darah Pada Pasien Diabetes Mellitus - Selviana Tawil; Arindah Saputri; Muhammad Asri; Ria Rizka Mansur; Musdalipa Musdalipa (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
One of the most common non-communicable diseases in society is Diabetes Mellitus. Changes in food intake in society, especially in big cities, from traditional foods to western foods are one of the risks of increasing blood glucose levels, especially carbohydrate. The purpose of this study was to determine the effect of carbohydrate on blood glucose levels in diabetes mellitus patients at the outpatient clinic of Sudiang Raya Health Center, Makassar City. This study used a quantitative research type with a cross-sectional approach. The population in this study were diabetes mellitus patients at the outpatient clinic of Sudiang Raya Health Center, totaling 149 respondents and a sample of 60 respondents was obtained by sampling using the accidental sampling technique. The collection used the SQ-FFQ questionnaire while random blood glucose data were obtained from laboratory results and then analyzed using the Correlation test. The results showed that the effect of carbohydrate intake (p = 0.290) on blood glucose levels in diabetes mellitus patients. The conclusion in this study is that there is no effect between carbohydrate on blood glucose levels in diabetes mellitus patients.